2010
DOI: 10.1038/nnano.2010.241
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional carbon-nanotube cellular endoscopes

Abstract: Glass micropipettes, atomic force microscope tips and nanoneedles can be used to interrogate cells, but these devices either have conical geometries that can damage cells during penetration or are incapable of continuous fluid handling. Here, we report a carbon-nanotube-based endoscope for interrogating cells, transporting fluids and performing optical and electrochemical diagnostics at the single organelle level. The endoscope, which is made by placing a multiwalled carbon nanotube (length, 50-60 µm) at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
224
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(226 citation statements)
references
References 33 publications
2
224
0
Order By: Relevance
“…Due to their high-aspect ratio geometry and exceptionally sharp tips, nanopipettes offer an important advantage over conventional nanopores as they can be easily adapted for use in single cell interrogation 15,16 and as a macroscopic delivery vehicle for intracellular injection. [17][18][19][20][21][22] . To date, delivery of molecules has so far only been quantified in close proximity to the tip by using fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high-aspect ratio geometry and exceptionally sharp tips, nanopipettes offer an important advantage over conventional nanopores as they can be easily adapted for use in single cell interrogation 15,16 and as a macroscopic delivery vehicle for intracellular injection. [17][18][19][20][21][22] . To date, delivery of molecules has so far only been quantified in close proximity to the tip by using fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have demonstrated the insertion of high aspectratio nanostructures for molecular delivery with minimal cell perturbation, suggesting that nanomaterials may pass through the cell membrane without dire consequences (19)(20)(21)(22)(23)(24). Extending this approach, Na et al (25) showed a nanowire "sandwich assay" in which nanowires approximately 100 nm in diameter functionalized with antibodies penetrate the cell with limited toxicity and can bind specific enzymes for extraction.…”
mentioning
confidence: 99%
“…Researchers must investigate the reactivity of a protein with its physiological partners to understand its role in cellular pathways; concentration measurements alone could be misleading, because the local environment of a protein can drastically alter its activity. Emerging capillary micro-/nanofabrication technologies allow the chemical reactivity of the target species to be investigated (3,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Allbritton and coworkers (11,12) embarked on the development of this technology and used capillary electrophoresis to analyze intracellular kinase activity.…”
mentioning
confidence: 99%